Crystal structures, computational studies, and Hirshfeld surface analysis on 7-hydroxy-4-methyl-2H-chromen-2-one and 7-hydroxy-4-methyl-8-nitro-2H-chromen-2-one - Odame, Felix; Boadi, Nathaniel Owusu; Nanga, Salifu; Aniagyei, Albert; Hosten, Eric (European Journal of Chemistry, 2025)
7-Hydroxy-4-methyl-2H-chromen-2-one and 7-hydroxy-4-methyl-8-nitro-2H-chromen-2-one have been synthesized. The compounds have been characterized using IR, NMR, GC-MS, and elemental analysis. The single-crystal X-ray structure of the compounds showed that compound 1 was crystallized in the orthorhombic space group P212121 while compound 2 crystalized in the monoclinic space group P21/c. A comparison of the computed and experimental bond lengths and bond angles showed good agreement among the data. A Hirshfeld surface analysis showed that the H∙∙∙O/O∙∙∙H interaction was the most prominent molecular interaction for both compound 1 H∙∙∙O/O∙∙∙H (34.4%) and compound 2 H∙∙∙O/O∙∙∙H (48.6%).